Cancer risk in oil refinery workers: a pooled mortality study in Italy - Bonzini, Matteo; Grillo, Paolo; Consonni, Dario; Cacace, Raquel; Ancona, Carla; Forastiere, Francesco; Cocco, Pier Luigi; Satta, Giannina; Boldori, Liana; Carugno, Michele; Pesatori, Cecilia Angela (La Medicina del Lavoro, 2019)
Background: Oil refinery workers are exposed to several well-established carcinogens and working in this type of industry has been classified by IARC as probable carcinogen to humans (Group 2A). Objectives: To examine the mortality experience of workers employed in four Italian oil refineries. Methods: The cohort included 5112 male workers ever employed between 1949 and 2011. The average follow-up period was 49 years. Standardized mortality ratios (SMR) and 95% Confidence Intervals (CI) were calculated using as reference age-gender-calendar specific regional rates. Analyses by duration of employment and latency were performed. Results: In the whole cohort, pleural cancer (6 deaths, SMR 1.59; 95% CI 0.71-3.53), brain cancer (14 deaths, SMR 1.47; 95% CI 0.87-2.49) and lymphatic leukemia (LL) (8 deaths, SMR 1.81; 95% CI 0.91-3.62) showed increased risks. All pleural cancers occurred after 10 years of latency and the highest risk was observed among workers with duration ≥20 years; the brain cancer excess was confined in the shortest duration and latency. The LL (and chronic lymphatic leukemia in particular) excess regarded workers with latency and duration longer than 20 years. Four deaths from acute myeloid leukemia (AML) were observed and all occurred after 20 years of latency (SMR 1.55, 95% CI 0.58-4.12); a two-fold-increased risk was observed in the longest duration. No increased risk for skin cancer has been observed in our study population. Conclusion: Our findings are consistent with recent evidence of an increased mortality from pleural and hematopoietic malignancies (AML and LL) among oil refinery workers. However, the lack of individual quantitative exposure data and the small number of observed events prevent the identification of the possible causal role of individual chemicals, including benzene, especially at the current very low exposure levels.